Boosting photovoltaic performance of ternary organic solar cells by integrating a multi-functional guest acceptor. (December 2021) - Yin, Yuli; Zhan, Lingling; Liu, Ming; Yang, Chongqing; Guo, Fengyun; Liu, Yi; Gao, Shiyong; Zhao, Liancheng; Chen, Hongzheng; Zhang, Yong
Abstract: Constructing ternary structure is one of the most effective design strategies to break the efficiency ceiling of traditional binary organic solar cells (OSCs). Here, a new Y-series non-fullerene acceptor (Y-T) featuring 1, 3-diethyl-2-thiobarbituric acid (DTBA) end groups is developed as a third component for the classical PM6:Y6 binary system. The champion power conversion efficiency of ternary OSCs is increased from 15.64% to 17.37% via incorporating 10 wt% Y-T, with the simultaneously enhanced open-circuit voltage ( V oc ) of 0.865 V, a short-circuit current density ( J sc ) of 26.90 mA/cm 2, and a fill factor (FF) of 74.97%. The positive contribution of Y-T in the ternary blend can be ascribed to the improved spectroscopic complementarity and enhanced exciton utilization ratio due to the additional energy transfer process. Moreover, Y-T guest acceptor plays a critical role in adjusting the active layer morphology and facilitating three-dimension phase separation, resulting in a balanced charge transport and enhanced FF of ternary OSCs. This work provides insight into the molecular design of non-fullerene acceptor and suggest guidelines to rationally select guest component for ternary OSCs. Graphical Abstract: Ternary solar cells architecture has proven to be effective for overcoming the potential limit of binary solar cells. Here we report a new Y-series guest acceptor Y-T with integrated functions as an energy mediator, a morphological regulator, and an energy transfer donor, which forms alloy acceptor when mixed with the host acceptor Y6 and yields an impressive power conversion efficiency in ternary devices. ga1 Highlights: A multi-functional Y-series guest acceptor, Y-T, is developed for the state-of-the-art PM6:Y6 binary system. Ternary devices delivers a PCE of 17.37% efficiency with the simultaneously enhanced photovoltaic parameters. Morphology of ternary film was synergistically optimized by the formation of three-dimensional alloyed microstructure.